Sovereigns versus Banks: Credit, Crises, and Consequences - Òscar Jordà; Moritz Schularick; Alan M. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2013)
Two separate narratives have emerged in the wake of the Global Financial Crisis. One speaks of private financial excess and the key role of the banking system in leveraging and deleveraging the economy. The other emphasizes the public sector balance sheet over the private and worries about the risks of lax fiscal policies. However, the two may interact in important and understudied ways. This paper studies the co-evolution of public and private sector debt in advanced countries since 1870. We find that in advanced economies financial stability risks have come from private sector credit booms and not from the expansion of public debt. However, we find evidence that high levels of public debt have tended to exacerbate the effects of private sector deleveraging after crises, leading to more prolonged periods of economic depression. Fiscal space appears to be a constraint in the aftermath of a crisis, then and now.
Keywords: C14; C52; E51; F32; F42; N10; N20; 330; leverage; booms; recessions; financial crises; business cycles; local projections; Finanzkrise; Private Verschuldung; Öffentliche Schulden; Konjunktur; Industrieländer